The Effective Management of Idiopathic Intracranial Hypertension Delivered by In-person and Virtual Group Consultations: Results and Reflections from a Phase One Service Delivery. (4th July 2021) - Wong, S. H.; Barrow, N.; Hall, K.; Gandesha, P.; Manson, A.
ABSTRACT: The increasing incidence of idiopathic intracranial hypertension (IIH) with the obesity epidemic is leading to increased pressures on service capacity. Evidence shows that group consultations (GCs) deliver effective, person-centred healthcare, but the feasibility for IIH is unknown. We set out to develop and test a safe and effective GC service for IIH. Through an interactive approach, we co-designed a bespoke in-person and virtual GC model, where patients are reviewed in a group setting. Improvements were made following each session following patient input and team reflections. Outcomes measured included patient satisfaction, self-perceived health literacy, and successful implementation of the GCs. During the pilot, eight in-person GCs were delivered: once-monthly (Oct–Dec 2019), then twice-monthly (Jan–Feb 2020). Feedback was received from 49/53 patients. 100% felt more satisfied and heard, 100% felt more involved in decision-making, 98% had a better understanding of their condition, 96% felt more able to cope with their condition and keep themselves healthy, 94% rated this as a positive experience, and 90% reported improved access and more time with their clinician compared with existing 1:1 appointments. Since September 2020, in response to the COVID-19 pandemic, we transitioned to weekly virtual GCs, receiving overwhelmingly positive feedback (median scores: patient satisfaction 9.5/10; being listened to by clinician 10/10; involved by clinician in treatment decisions 10/10; clinician explanation of treatment 10/10; and opportunity to discuss condition or treatment 10/10). GCs are safe and effective for IIH, and preferred in our patient cohort. This allowed ongoing high-quality, person-centred care despite challenges from the COVID-19 pandemic.